Pabst wieder sehen - Koerber, Martin; Jacobsen, Wolfgang (Germany, 1997)
The film is accompanied with outtakes and intakes (14 min.), sound document with memories of the assistant director Mark Sorkin (49 min.).
Keywords: Documentary films